ALASAN UNI EROPA DALAM MEMPERTAHANKAN KEBIJAKAN SUBSIDI PERIKANAN PASCA REFORMASI COMMON FISHERIES POLICY (CFP) TAHUN 2002 - , FEMBIARTA BINAR P ([Yogyakarta] : Universitas Gadjah Mada, 2013)
After the reform of Common Fisheries Policy (CFP) in 2002, the European Union issued fisheries subsidies with the original purpose to keep the waterâs environment and European marine resources. However, this policy actually have an impact on the environmental damage such as overfishing that threatens fish stocks in European waters, food security, long-term economic, and political integration of the European Union in the future. Fisheries subsidies become a controversial policy because it proved with the negative impact on the environment. By looking at the political processes in three pillars of the European Union as a supranational state reflection: European Commission, European Parliament and Council of the European Union, resulted a decision that fisheries subsidies will continue with allocate fund 6.5 billion euro start from 2014 until 2020. Some countries support this policy as beneficial subsidies, but the others countries argue that subsidies is a blind spent. Conflicts of the member stateâs interest behind the fisheries subsidies and the political dynamics background become focus of the research to find out the reasons and justification of the European Union to still maintain fisheries subsidies.